Acoustic Aerosol Delivery: Assessing of Various Nasal Delivery Techniques and Medical Devices on Intrasinus Drug Deposition - Lara Leclerc; Nathalie Prévôt; Sophie Hodin; Xavier Delavenne; Heribert Mentzel; Uwe Schuschnig; Jérémie Pourchez (MDPI AG, 2023)
This study aims to evaluate the impact of the nasal delivery technique and nebulizing technologies (using different frequencies of oscillating airflow) for acoustic aerosol targeting of maxillary sinuses. Sodium fluoride (chemical used as a marker), tobramycin (drug used as a marker) and 99mTc-DTPA (radiolabel aerosol) were used to assess the intrasinus aerosol deposition on a nasal cast. Two commercial medical devices (PARI SINUS nebulizer and NL11SN ATOMISOR nebulizer) and various nasal delivery techniques (one or two nostrils connected to the aerosol inlet, the patient with the soft palate closed or open during the acoustic administration of the drug, the presence or not of flow resistance in the nostril opposite to the one allowing the aerosol to be administered) were evaluated. The closed soft palate condition showed a significant increase in drug deposition even though no significant difference in the rest of the nasal fossae was noticed. Our results clearly demonstrated a higher intrasinus aerosol deposition (by a factor 2-3; respectively 0.03 ± 0.007% vs. 0.003 ± 0.0002% in the right maxillary sinus and 0.027 ± 0.006% vs. 0.013 ± 0.004% in the left maxillary sinus) using the acoustic airflow generated by the PARI SINUS compared to the NL11SN ATOMISOR. The results clearly demonstrated that the optimal conditions for aerosol deposition in the maxillary sinuses were obtained with a closed soft palate. Thus, the choice of the nebulizing technology (and mainly the frequency of the pulsating aerosol generated) and also the recommendation of the best nasal delivery technique are key factors to improve intrasinus aerosol deposition.